2016
DOI: 10.1523/eneuro.0056-14.2016
|View full text |Cite
|
Sign up to set email alerts
|

Synergism and Combinatorial Coding for Binary Odor Mixture Perception inDrosophila

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…These results suggest: (i) mixtures of odorants exhibited improved attractiveness to mosquitoes relative to single odorants; and (ii) the odor mixtures work in a manner that is largely dependent on both the proportion and dilution of the ingredient. Our findings are consistent with the synergism and combinatorial coding for mixture perception reported for Drosophila [40].…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest: (i) mixtures of odorants exhibited improved attractiveness to mosquitoes relative to single odorants; and (ii) the odor mixtures work in a manner that is largely dependent on both the proportion and dilution of the ingredient. Our findings are consistent with the synergism and combinatorial coding for mixture perception reported for Drosophila [40].…”
Section: Discussionsupporting
confidence: 92%
“…Previously, Rospars et al (9) found that responses of olfactory receptor neurons to some simple binary mixtures were largely consistent with a similar model and could display both hyper- and hypoadditivity. Related results for binary mixtures have also been reported for neurons in the accessory olfactory system (10) and in the antennal lobes of Drosophila (11) and locust (12). Cruz and Lowe (13) subsequently developed a biophysically motivated version of this model and applied it to glomerular imaging.…”
supporting
confidence: 66%
“…The amount (dose) and proportion of chemical mixtures in compounds can play critical roles in insect response and are important considerations in attractant development [55]. As the commercial lure combination of ingredients (by proportion) was not modified in this study, it was evident that dose alone had a significant effect on responses between the two species.…”
Section: Discussionmentioning
confidence: 67%